Studi Literatur Analisis Algoritma Pemrograman Pengaruh Computational Thinking pada Pembelajaran Matematika - Sherly Putri Revika; Yahfizham Yahfizham (STIKes Ibnu Sina Ajibarang, 2024)
In the modern age, technological advancements are undeniably progressing at a rapid pace. Throughout its rapid progress, technology has had an impact on various aspects of life, and education is one of the fields affected by it. In the context of technological advancement, both teachers and students acquire important skills known as computational thinking. Computational thinking refers to the ability to systematically solve problems using logical reasoning and step-by-step decision-making for problem-solving. Computational thinking has a direct relationship with students' mathematical learning, especially in the process of tackling mathematical problems. The purpose of this research is to investigate the influence of computational thinking on mathematics learning, with a specific focus on algorithm analysis in programming. The research methodology involves a comprehensive analysis of related literature to delve into the research topic, using a literature review method. The results of this research indicate that computational thinking can be measured using specific indicators that play a crucial role in mathematics learning. Students' ability to apply computational thinking techniques to solve mathematical problems can be determined based on indicators such as decomposition, pattern recognition, abstraction, algorithmic thinking, and generalization.